2022
DOI: 10.1155/2022/5651506
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Symptom Duration and Serologic Factors in the Relapse of IgG4-Related Ophthalmic Disease following Surgery: A Retrospective Cohort Study

Abstract: IgG4-related disease (IgG4-RD) affects multiple organs and is characterized by immune-mediated inflammation and fibrosis; IgG-RD affecting orbital tissue is known as IgG4-related ophthalmic disease (IgG4-ROD). This research is aimed at exploring whether symptom duration and common serologic factors, such as IgG, IgE, and eosinophils, are potential risk factors for IgG4-ROD patient relapse after surgery and identifying possible causes of the positive correlation between symptom duration and relapse. This retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies had shown that serum IgG4, RF, and male gender were risk factors for recurrence of IgG4-ROD treated with glucocorticoid therapy [28][29][30] . Liu et al [31] found that IgG4-ROD symptom duration was significantly positively correlated with relapse rate. Our study showed that gender, extraocular muscle thickening, nerve thickening, sinusitis, IgG4 and RF were not risk factors for recurrence of LGBLEL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that serum IgG4, RF, and male gender were risk factors for recurrence of IgG4-ROD treated with glucocorticoid therapy [28][29][30] . Liu et al [31] found that IgG4-ROD symptom duration was significantly positively correlated with relapse rate. Our study showed that gender, extraocular muscle thickening, nerve thickening, sinusitis, IgG4 and RF were not risk factors for recurrence of LGBLEL.…”
Section: Discussionmentioning
confidence: 99%
“…Serological factors, including high serum IgG4 level, elevated serum IgE, and elevated eosinophils, are known to be associated with IgG4-ROD relapse [ 7 , 40 ]. In our study, serum IgG4 levels before initial steroid therapy were significantly higher in the IV group than in the oral group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high serum indexes are more sensitive to the immune response, which makes the disease more likely to relapse. Furthermore, Th2 cells can secrete specific cytokines, such as IL-13, IL-5 and IL-4, to cause allergy and immune abnormalities, 48 and the presence of allergies can increase the number of circulating Th2 memory cells, which increases atopy and enhances Th2 responses, such as increasing serum IgG, IgE and eosinophil levels, 49 in IgG4-RD. 48,50 High multiple organ involvement and proximal bile duct stenosis rates might reflect the severity and activity of IgG4-RD, which helps to predict the relapse of the disease.…”
Section: Discussionmentioning
confidence: 99%